Functionalized conductive polymer composites for tissue engineering and biomedical applications- a mini review - Gayathri, V.; Khan, Tabrej; Gowtham, M.; Balan, R.; Sebaey, Tamer A. (Frontiers in Bioengineering and Biotechnology, 2025)
Tissue engineering (TE) has emerged as a promising therapeutic strategy, employing artificial scaffolds to regenerate functional cardiac tissue and offering new hope for innovative treatment approaches. A straightforward method for producing biodegradable, conductive polymer-based composites involves blending conductive polymers directly with biodegradable ones. This approach’s flexibility enables the development of diverse biodegradable, conductive polymer scaffolds, which have been extensively explored in tissue engineering and regenerative medicine. While this technique successfully combines the advantages of both polymer types, it may face challenges such as potential compromises in conductivity and biodegradability. This review emphasizes the potential to tailor degradation rates and conductivity by selecting appropriate polymer types and ratios, ensuring adaptability for various biomedical applications.